Preparation and electrochemical properties of Al/TiB2/β-PbO2 layered composite electrode materials for electrowinning of nonferrous metals. Issue 15 (15th October 2018) - Han, Zhaohui; Xu, Lei; Kannan, Chandrasekar Srinivasa; Liu, Jianhua; Koppala, Sivasankar; Ju, Shaohua; Zhang, Libo
Abstract: In this paper, an Al/TiB2 layered composite was prepared by plasma spraying for use as the base material to reduce resistivity and improve electrochemical performance in an electrode. The β-PbO2 coating was prepared by electrochemical deposition. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to study the Al/TiB2 composite and the β-PbO2 coating. The electrochemical performance of the Al/TiB2 /β-PbO2 and Ti/β-PbO2 composites was studied by linear sweep voltammetry (LSV), Tafel polarization curves (Tafel) and electrochemical impedance spectroscopy (EIS). The results indicate that Al/TiB2 /β-PbO2 composite electrode materials with a uniform structure were successfully prepared by plasma spraying and electrochemical deposition. The structure of the Al/TiB2 composite improves the conductivity of the electrode matrix, the optimal value of conductivity is 2.76 × 10 7 S m −1, and the optimal value of density is 8.758 g cm −3 for β-PbO2 coating. The composite also decreases the charge resistance in the double layer structure of the electrode surface, accelerating the charge transfer rate. Compared with the Ti matrix, the Al/TiB2 /β-PbO2 exhibited the best corrosion-resistant performance and electrochemical catalytic activity for electrowinning of nonferrous metals.